INTERNATIONAL TEACHING PRACTICUM IN BANGLADESH: AN INVESTIGATION OF TESOL PRE-SERVICE TEACHERS’ PROFESSIONAL DEVELOPMENT EXPERIENCES (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ International teaching practicum (ITP) is seen as an avenue for future teachers to broaden their world views and enhance their personal and professional development. Based on two teachersâ€™ experiences of ITP in Bangladesh, in comparison to their teaching practicum experiences in Malaysia, this paper aims to examine the impact of the ITP on their professional development as future English language teachers.Methods â€“ Two female teachers were involved in this qualitative research, whereby data were obtained from the teachersâ€™ observations, reflective journals and face-to-face interview. Interpretative Phenomenological Analysis (IPA) was used to analyze the data.Findings â€“ Findings indicate that the two teachers had gained positive professional development experiences as a result of participating in the ITP, especially in terms of these four aspects: (i) confidence; (ii) teaching skills; (ii) perspective on education and culture; and (iv) interpersonal skills.  Significance â€“ The study indicates that ITP could be an alternative platform for future teachers to gain positive professional development experiences, which then would prepare them for the challenging teaching environment.